PENERAPAN UX GAMIFICATION PADA APLIKASI PEMESANAN LAYANAN SALON BERBASIS WEBSITE MENGGUNAKAN CODEIGNITER PADA SALON SEVENTYRAZOR - Andri Prasetyo; Samsul Arifin; Linda Suvi Rahmawati (Jurnal Technopreneur (JTech), 2019)
Salon seventyrazor initially used manual recording in serving the queue, Customers who come to register first with the administrative officer. Once recorded in the Microsoft Excel application, will be informed whether there is a queue or directly processed to the Barberman officer. When a customer makes an order through Whatsapp, the process is the same. Estimates for each hair cut are 30 to 45 minutes for each customer. The creation of a Website-Based Salon Service Order Application using Codeigniter on Seventyrazor Salon with the application of gamification as a solution in handling queuing reservations at Barbershop seventyrazors, especially in reducing the number of queues at the location and order cancellations that often occur. In this study the authors used the User-Centered-Design approach with the gamification method as a method of system development and using UML (Unified Modeling Language) as a tool in modeling the system to be built. Based on the research that has been done, it can be concluded that the website-based queue ordering application at Barbershop Seventyrazors can accelerate the recording of transactions that will occur today and tomorrow, and customers do not need to queue long at Barbershop because they already know their queue hours. transaction data processing in making monthly reports faster so that it can accelerate the generation of monthly income reports. The application created is a web-based application using a codeigniter framework.